HUBUNGAN ANEMIA DALAM KEHAMILAN DENGAN KEJADIAN PERDARAHAN POSTPARTUM PRIMER di RSUD PUTRI HIJAU MEDAN PERIODE JANUARI 2020-JANUARI 2021 - MEIYANA SINAGA SINAGA (Universitas Prima Indonesia, 2022)
This study aims to determine the relationship between anemia in pregnancy and the incidence of primary postpartum hemorrhage at Putri Hijau Hospital, Medan for the period January 2020 - January 2021. The research method used is an analytic case-control approach. Data were taken from the Register and Patient Medical Records. The population in this study was 447 mothers who gave birth during January 2020 – January 2021. The number of case samples and control samples was made in a 1:1 ratio by following the number of case samples that met the inclusion and exclusion criteria. Bivariate analysis using the Chi Square test found the results: p = 0.000 (p <α, = 0.05), then Ho was rejected, which means that there is a relationship between Anemia in Pregnancy and Primary Postpartum Bleeding Incidence at Putri Hijau Hospital Medan. The strength of the relationship between the two variables is seen based on the contingency coefficient, which is 0.631 which means the strength of the relationship is strong. Then the results of the Odds Ratio (OR) obtained OR = 105 [95% CI 17.8 - 618.7] which means that the range of 17.8 - 618.7 does not exceed the value of 1, so mothers giving birth with anemia in their pregnancy are likely to have primary postpartum hemorrhage. 105 times greater than women who gave birth without anemia in their pregnancy. Based on the results of research and discussion on the relationship between anemia and the incidence of primary postpartum hemorrhage at the Putri Hijau Hospital, Medan for the January 2020 – January 2021 period, it is expected to increase regular health promotion regarding pregnancy and childbirth by involving the role of cadres in providing counseling and involving the role of husband/family in health. pregnant women to minimize the risk of anemia in pregnancy and primary postpartum hemorrhage.